Do we face a credit crunch? - Klaus-Jürgen Gern; Nils Jannsen (Kiel Institute for the World Economy (IfW), 2009)
The weakness of credit growth in the United States and Europe has given rise to concerns that the financial crisis has led to a credit crunch which has deepened the recession in the real economy and poses a serious threat to the recovery that seems to have started in the most recent months. In this contribution we find that so far the development of credit aggregates and interest rates for loans does not provide strong evidence for a supply restraint that goes beyond hat could be expected given the deterioration of the quality of borrowers against the background of the exceptionally severe economic downturn. Still, the behaviour of interest rate spreads in the United States does indicate that the effectiveness of monetary policy is reduced for the time being as a result of distress in the financial sector, and we see some risks that inappropriate bank capitalization may restrain credit growth and threaten the current recovery, especially in Germany where core capital is low by international standards. Policy measures to avoid a credit crunch should focus on preventing undercapitalization of banks from becoming a serious limitation to credit growth.
Keywords: 330; Kreditmarkt; Kreditrationierung; Zinsstruktur; Bankenpolitik; Eigenkapital; Deutschland